The Effect Of Financial Distress And Audit Delay On Auditor Switching On Banking Companies Listed On The Indonesia Stock Exchange - Deliana deliana; Abdul Rahman; Lifian Monica; Ariama Susanti (Universitas Islam Bandung, 2022)
This study aims to prove the effect of financial distress and audit delay on auditor switching. The study was conducted in banking companies listed on the Indonesia Stock Exchange. The population of this study is the financial statements of banking companies listed on the Indonesia Stock Exchange. in 2016-2019 as many as 45 companies. Determination of the sample using purposive sampling using certain criteria, companies that meet the criteria are 37 companies with 4 years of observation, so the number of observations in this research is 148. Tests were carried out using logistic regression analysis with the help of SPSS software. The results of this study indicate that financial distress and audit delay have no effect on auditor switching.